Cognitive deficits in unipolar old-age depression: a population-based study. Issue 5 (10th July 2013) - Pantzar, A.; Laukka, E. J.; Atti, A. R.; Fastbom, J.; Fratiglioni, L.; Bäckman, L.
Abstract : Background: There is substantial variability in the degree of cognitive impairment among older depressed persons. Inconsistencies in previous findings may be due to differences in clinical and demographic characteristics across study samples. We assessed the influence of unipolar depression and severity of depression on cognitive performance in a population-based sample of elderly persons aged ⩾60 years. Method: Eighty-nine persons fulfilled ICD-10 criteria for unipolar depression (mild, n  = 48; moderate, n  = 38; severe, n  = 3) after thorough screening for dementia (DSM-IV criteria), psychiatric co-morbidities and antidepressant pharmacotherapy. Participants ( n  = 2486) were administered an extensive cognitive test battery. Results: Moderate/severe unipolar depression was associated with poorer performance on tasks assessing processing speed, attention, executive function, verbal fluency, episodic memory and vocabulary. Mild depression was associated with poorer performance in processing speed, and few differences between mild and moderate/severe depression were observed. No association between depression and short-term memory, general knowledge or spatial ability was observed. Increasing age did not exacerbate the depression-related cognitive deficits, and the deficits remained largely unchanged after excluding persons in a preclinical phase of dementia. Furthermore, depression-related cognitive deficits were not associated with other pharmacological treatments that may affect cognitive performance. Conclusions: Cognitive deficits in unipolar old-age depression involve a range of domains and the cognitive deficits seem to follow the spectrum of depression severity. The finding that mild depression was also associated with poorer cognitive functioning underscores the importance of detecting mild depression in elderly persons.